Effectiveness of the Principle of Dominus Litis in Enforcement of Criminal Procedure with Legal Certainty - Saputra, Dadin Eka (Journal of Law Science, 2025)
Study This to study effectiveness implementation the principle of dominus litis in system enforcement criminal procedure law in Indonesia which emphasizes importance certainty law. The principle of dominus litis as principle that prosecutor's office own control main in the investigation and prosecution process, plays a role important in system justice criminal. However, its implementation must balanced with strengthening harmonization regulation legislation related For avoid overlap overlap authority between institution enforcer law, in particular between police and prosecutors. Findings study show that implementation the principle of dominus litis which is not notice principle differentiation functional and provisions of the Criminal Procedure Code can cause conflict authority and inhibit achievement effective and efficient justice. Therefore? that, recommendation given so that the government in formulate policy more notice protection law for public seeker justice, with to uphold principle certainty law as guidelines main judicial process criminal . Research This give contribution important in understanding and development system justice just and based on criminal law certainty law